Comparative Cytotoxicity and Intracellular Accumulation of Five Polybrominated Diphenyl Ether Congeners in Mouse Cerebellar Granule Neurons - Huang, Suping C. (Oxford University Press, 2010)
Polybrominated diphenyl ethers (PBDEs), a group of flame retardants comprising 209 congeners, have become widespread environmental pollutants. High levels of PBDEs have been detected in human tissues, particularly in North America, and body burden is especially high in infants and toddlers because of exposure through breast milk and house dust. Increasing evidence, provided by animal studies, suggests that PBDEs are developmental neurotoxicants, although the underlying mechanisms are still unknown. Various PBDEs have been reported to cause oxidative stress and to induce apoptotic cell death in several cell types. In the present study, we investigated the comparative neurotoxicity in mouse cerebellar granule neurons of five brominated diphenyl ether (BDE) congeners, chosen among the most commonly found at the highest levels in human tissues. All BDE congener tested (BDE-47, BDE-99, BDE-100, BDE-153, and BDE-209) decreased cell viability and induced apoptotic cell death, which was prevented by antioxidants. They also caused oxidative stress, as indicated by an increase in reactive oxygen species and in lipid peroxidation. For all end points measured, the potency ranking of the congeners was BDE-100 > BDE-47 > BDE-99 > BDE-153 >> BDE-209. Measurement of BDE congener levels in neurons after exposure to different concentrations showed a significant accumulation in cells, which followed the same relative ranking. The findings suggest that all BDE congeners tested exhibit the same general mode of action (induction of oxidative stress–mediated apoptosis) and that the ability of each isomer to elicit such effects is dependent upon their accumulation in neurons, particularly in the microsomal fraction and the mitochondria.